1982
DOI: 10.1128/aac.21.1.146
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acyclovir and interferon on human hematopoietic progenitor cells

Abstract: Continuous in vitro exposure of human bone marrow cells to acyclovir (-200 ,uM) or human leukocyte interferon (-250 U/ml) caused 50% inhibition of granulocyte colony-forming cell differentiation. Colonies expressed in the presence of either agent were reduced both in size and number. Erythroid progenitors were more resistant than granulocyte progenitors to the antiproliferative effects of acyclovir. Progenitor cells of patients recovering from cytotoxic chemotherapy were no more sensitive to the effects of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1983
1983
1993
1993

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
(15 reference statements)
1
8
0
Order By: Relevance
“…Thus, uninfected cells escape toxicity of the activated ACV and BVdU at concentrations far in excess of those demonstrating antiviral activity. The effects of ACV on CFU-c in our study are similar to those described in previous reports (18,20). We observed inhibition of ConA and PHA stimulation by ACV at concentrations somewhat lower than those described in earlier reports (17,27), which is probably attributable to variability of responsiveness between different donors (17) or to technical differences in these assays.…”
Section: Resultssupporting
confidence: 79%
“…Thus, uninfected cells escape toxicity of the activated ACV and BVdU at concentrations far in excess of those demonstrating antiviral activity. The effects of ACV on CFU-c in our study are similar to those described in previous reports (18,20). We observed inhibition of ConA and PHA stimulation by ACV at concentrations somewhat lower than those described in earlier reports (17,27), which is probably attributable to variability of responsiveness between different donors (17) or to technical differences in these assays.…”
Section: Resultssupporting
confidence: 79%
“…In contrast, these investigators reported that the ID50 of BVdU for CFU-C was 120 FtM (40 ,ug/ml) compared with 197 ,ug/ml determined by our assay. Such variability between in vitro assays for antiviral toxicity has been observed previously (12,13) (19) demonstrated no consistent suppression of antigen-or mitogen-induced lymphocyte blastogenesis by acyclovir (ACV) below concentrations of 50 ,ug/ml (11.5 F.M). Levin et al (9) demonstrated suppression of blastogenesis only at ACV concentrations of 100 ,uM (23 ,ug/ml).…”
mentioning
confidence: 88%
“…A wide range of ACV con centrations had no effect on the viability of Mp and increased rather than reduced the surviving cell numbers and their protein con tent. Previous reports [6,7,18] indicated that ver)' high concentrations of ACV may inhibit cell growth and DNA synthesis of normal cells. In contrast, cells which were transfected with ultraviolet-irradiated HSV and ex pressed a thymidine-kinase-positive pheno type, were significantly more sensitive to inhi bition by ACV [18].…”
Section: Discussionmentioning
confidence: 99%
“…In uninfected cells, the uptake of ACV is poor, little phosphorylation takes place and the af finity of the phosphorylated drug for cellular a-DNA polymerase is low. However, some studies [6,7] indicate that higher concentra tions may inhibit cell division and synthesis of cellular DNA. Studies on the in vitro devel opment of hematopoietic progenitor cells and on the immune response of in vitro-stimulated peripheral blood mononuclear cells also indi cate that high, but not therapeutic, concentra tions of ACV may influence these functions [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%